Silent Conversations in Rudyard Kipling’s Kim and Ruskin Bond’s Rusty novels - Ghosh, Debasree (SARE: Southeast Asian Review of English, 2021)
The essay undertakes an analysis of the connections and conversations between Rudyard Kipling’s Kim and Ruskin Bond’s Rusty novels, which are largely autobiographical. It considers India’s journey into the postcolonial age and its impact on the Anglo-Indian lineage which both writers share, while it traces the implicit dialogue between the writers and their protagonists which underpin Bond’s novels. It undertakes a close reading of the texts to examine the evolution of English literature in India and it seeks to interrogate the divided identities of the author and protagonists.